Altered Functional Connectivity in White and Gray Matter in Patients With Multiple Sclerosis - Huang, Jing; Li, Muwei; Li, Qiongge; Yang, Zhipeng; Xin, Bowen; Qi, Zhigang; Liu, Zheng; Dong, Huiqing; Li, Kuncheng; Ding, Zhaohua; Lu, Jie (Frontiers in Human Neuroscience, 2020)
Background: Cortical connectivity abnormalities have revealed widespread alterations in patients with multiple sclerosis (MS); however, brain function alterations in white matter (WM) are relatively understudied. Purpose: To identify the functional connectivity in both WM and gray matter (GM) in patients with MS by using the functional MRI, and the correlations between these functional changes and disability accumulation, lesion ratio. Materials and Methods: For this retrospective study, thirty-seven clinically definite MS patients and 43 age-matched healthy controls were included between 2010 and 2014. Resting-state functional magnetic resonance imaging (fMRI) was assessed. WFU Pick and JHU Eve atlas were used to define 82 GM and 48 WM regions in common space, respectively. The time courses of BOLD signal were averaged over each GM or WM region. The averaged time courses for each pair of GM and WM regions were correlated. All the 82 × 48 correlations for each subject formed a functional correlation matrix. Results: The MS patients had a decreased temporal correlation between the WM and GM regions. Eight WM bundles and 4 GM regions had significantly decreased mean correlation coefficients (CCs). More specifically, the WM functional alterations were negatively correlated with the lesion volume in the bilateral fornix and left cingulum, and the mean GM-averaged CC of the WM bundles was inversely correlated with the lesion ratio (r = - 0.37, P = 0.012). No correlations between these alterations and PASAT, EDSS scores were observed. Conclusions: These findings highlight current gaps in knowledge of the WM functional alterations in patients with MS and may link WM function with pathological mechanisms.